2007
DOI: 10.1007/s11156-007-0040-0
|View full text |Cite
|
Sign up to set email alerts
|

Change in value relevance of quarterly foreign sales data of U.S. multinational corporations after adopting SFAS 131

Abstract: Segment disclosure, SFAS 131, Quarterly disclosure, Value relevance, Geographic segment, F23, G14, M41,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
3
12
0
2
Order By: Relevance
“…A number of authors now question the quality of the financial information communicated through SFAS 131: "Managers have strong incentives to manipulate internal segment information used in performance evaluation" (Berger and Hann, 2003). Indeed, most North American studies of SFAS 131 have shown that the more firms communicate in terms of geographic segments, the greater the tendency to communicate results, notably abroad (Hope et al, 2009;Hossain, 2008). Some authors have also provided evidence that, even if IFRS 8 does not require provision of two levels of segment disclosures, in many instances the second-level disclosures (especially geographic disclosure) are finer and accordingly more useful for decision making (Nichols et al, 2012).…”
Section: Quality Of Segment Disclosure and Determination Of Hypothesesmentioning
confidence: 99%
“…A number of authors now question the quality of the financial information communicated through SFAS 131: "Managers have strong incentives to manipulate internal segment information used in performance evaluation" (Berger and Hann, 2003). Indeed, most North American studies of SFAS 131 have shown that the more firms communicate in terms of geographic segments, the greater the tendency to communicate results, notably abroad (Hope et al, 2009;Hossain, 2008). Some authors have also provided evidence that, even if IFRS 8 does not require provision of two levels of segment disclosures, in many instances the second-level disclosures (especially geographic disclosure) are finer and accordingly more useful for decision making (Nichols et al, 2012).…”
Section: Quality Of Segment Disclosure and Determination Of Hypothesesmentioning
confidence: 99%
“…Hossain and Marks () report similar results using quarterly information for U.S. multinational companies that voluntarily disclosed quarterly foreign and domestic sales prior to the implementation of SFAS 131. Hossain () observes a higher market reaction to the change in quarterly foreign sales after SFAS 131 relative to before SFAS 131. Lacina et al.…”
Section: Prior Researchmentioning
confidence: 99%
“…In this set of sensitivity tests, we include some additional variables that have been found to be related to abnormal returns around quarterly earnings announcements. Hossain and Marks () and Hossain () find that the abnormal returns around quarterly earnings announcements are related to the quarterly changes in domestic and foreign sales, with the financial market reacting more strongly to the change in foreign sales. However, Lacina et al.…”
Section: Supplemental Analysesmentioning
confidence: 99%
See 2 more Smart Citations